Labor Market Effects of Credit Constraints: Evidence from a Natural Experiment - Kumar, Anil; Liang, Che-Yuan (American Economic Journal: Economic Policy, 2024)
We exploit the 1997 and 2003 constitutional amendments in Texas-allowing home equity loans and lines of credit for nonhousing purposes-as natural experiments to estimate the effect of easier credit access on the labor market. Using state-level as well as micro data, we find that easier access to housing credit led to a notably lower labor force participation rate between 1997 and 2007. Our findings are remarkably robust to improved synthetic control methods based on insights from machine learning. Our research shows that negative labor market effects of easier credit access are important for assessing its stimulative impact on overall growth.
Keywords: Credit Constraints; Home Equity Loans; Natural Experiment; Labor Market